Le libre exercice du culte dans la République populaire de Chine (中華人民共和國) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMAIRE: 1. Une prémisse historique sur la Chine en tant que société multi-religieuse - 2. Les dispositions constitutionnelles relatives à la liberté de croyance avant 1982 - 3. La liberté religieuse dans l'actuelle Constitution de 1982 et la législation suivant en la matière - 4. Liberté religieuse et protection des droits de l'homme dans la Chine actuelle.The free exercise of Religion in People’s Republic of ChinaABSTRACT: After some historical reflections on the spread of multiple religious doctrines on the Chinese territory between the end of the XIX and the beginning of the XX century, the Author considers the attitude of the central government with respect to the right of religious freedom from the time of the Cultural Revolution to today, paying particular attention to the constitutional and criminal law provisions attached to this issue. It seems clear how the Chinese legal tradition is not based on a balance of interest theory as known in the Western legal systems, given the prevalence of the higher communist principles rooted in time. Last pages are reserved for the systematic violations of human rights reported by numerous international observatories, as well as the ancient grudge between China and the Holy See caused by the question of the appointment and formal recognition of new bishops. The provisional agreement signed on 22 September 2018, while marking a step towards finding a solution to this tensions, doesn’t offer a definitive solution to the problem.